In response to 'benefits and risks of intensive blood‐pressure lowering in advanced chronic kidney disease'. (12th March 2018) - Obi, Y.; Kalantar‐Zadeh, K.; Shintani, A.; Kovesdy, C. P.; Hamano, T.
Abstract : Click here to view the Letter to the Editor by Dr. Cheung et al .